IN SITU VASCULAR REGENERATION USING SUBSTANCE P-IMMOBILISED POLY(L-LACTIDE-CO-epsilon-CAPROLACTONE) SCAFFOLDS: STEM CELL RECRUITMENT, ANGIOGENESIS, AND TISSUE REGENERATION - Shafiq, M.; Jung, Y.; Kim, S. H. (AO RESEARCH INSTITUTE DAVOS-ARI, 2015)
In situ tissue regeneration holds great promise for regenerative medicine and tissue engineering applications. However, to achieve control over long-term and localised presence of biomolecules, certain barriers must be overcome. The aim of this study was to develop electrospun scaffolds for the fabrication of artificial vascular grafts that can be remodelled within a host by endogenous cell recruitment. We fabricated scaffolds by mixing appropriate proportions of linear poly (L-lactide-co-epsilon-caprolactone) (PLCL) and substance P (SP)-immobilised PLCL, using electrospinning to develop vascular grafts. Substance P was released in a sustained fashion from electrospun membranes for up to 30 d, as revealed by enzyme-linked immunosorbent assay. Immobilised SP remained bioactive and recruited human bone marrow-derived mesenchymal stem cells (hMSCs) in an in vitro Trans-well migration assay. The biocompatibility and biological performance of the scaffolds were evaluated by in vivo experiments involving subcutaneous scaffold implantations in Sprague-Dawley rats for up to 28 d followed by histological and immunohistochemical studies. Histological analysis revealed a greater extent of accumulative host cell infiltration and collagen deposition in scaffolds containing higher contents of SP than observed in the control group at both time points. We also observed the presence of a large number of laminin-positive blood vessels and Von Willebrand factor (vWF(+)) cells in the explants containing SP. Additionally, scaffolds containing SP showed the existence of CD90(+) and CD105(+) MSCs. Collectively, these findings suggest that the methodology presented here may have broad applications in regenerative medicine, and the novel scaffolding materials can be used for in situ tissue regeneration of soft tissues.
Keywords: BONE MORPHOGENETIC PROTEIN-2; EPIDERMAL-GROWTH-FACTOR; MYOCARDIAL-INFARCTION; PROGENITOR CELLS; BLOOD-VESSEL; GRAFTS; NANOFIBERS; DIAMETER; PEPTIDE; VIVO